Creating Corporate Sustainability in the Logistic Service Industry: The Effect of Management Transition and Digital Transformation - Masruroh; Alifia Andini Putri Pratama (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Dynamic transformations in the logistics services industry require companies to strengthen corporate sustainability through management adaptation and technological innovation. This study aims to investigate the influence of management transition and digital transformation on corporate sustainability in the context of logistics services industry companies in the Banten Region, as a representation of the logistics services sector in Indonesia. The approach used was quantitative by collecting data through a survey of 137 employees, then analyzed using the partial least squares–structural equation modeling method with SmartPLS 4 software. The results of the study show that management transition and digital transformation have a positive and significant effect on corporate sustainability, with digital transformation having a stronger influence in improving organizational efficiency and sustainability performance. These findings confirm that changes in managerial structures and the simultaneous integration of digital systems are able to strengthen the company’s sustainability orientation through operational innovation, leadership adaptability, and employee involvement in sustainability initiatives. This research contributes to management science by emphasizing the strategic role of managerial adaptability and digitalization in realizing long-term sustainability in logistics organizations, while providing practical insights for industry players and policymakers in designing sustainability-oriented transformation strategies in the digital era.